A technológiába vetett hit és a fenntarthatósági válság - Garai, Zsolt (Kultúratudományi Szemle, 2024)
Faith in technology and the sustainability crisis In this paper, in reviewing a book of Andras Gelencser, Abrandok buveleteben, I detect the emphasis given to technological development in high hopes of escaping ecological (environmental and energetic) catastrophe. I claim that Gelencser is quite realistic in doubting the related dogma. I review some well-grounded considerations for scepticism about omnipotence of technology in this respect and, particularly, the autonomy of the technological system and its characteristic bluffing in terms of efficiency (narrowly constructed). If a plan is a must in the present state of affairs, then it won t be reliable as it is based exclusively on future technological advancements. A viable plan, when evaluated on a conceptual level, should be able to limit the way of life that puts the technology in the centre, leading us to consume and distruct the very stage of human action. Paradoxically, however, technology remains a necessary condition for any plan but not without a companied effort to find a clear vision about what to grasp in the whirl of the ecological crisis.